2007
DOI: 10.1038/npre.2007.69.1
|View full text |Cite
|
Sign up to set email alerts
|

Promoter regions of many neural- and nutrition-related genes have experienced positive selection during human evolution

Abstract: Surveys of protein-coding sequences for signatures of positive selection in humans and chimpanzees have flagged surprisingly few genes known to be involved in neural or nutritional processes 1-5 , despite the pronounced differences between humans and chimpanzees in behavior, cognition, and diet 6-8 . It may be that most such differences are due to changes in gene regulation rather than protein structure 9 . Here, we present the first survey of promoter (5 -flanking) regions, which are rich in cis-regulatory se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 18 publications
2
44
0
Order By: Relevance
“…Finally, recent genome-wide surveys indicate that non-coding cis -regulatory sequences in close proximity to genes involved in neuronal cell adhesion (Prabhakar et al 2006) and neurogenesis (Haygood et al 2007) have undergone accelerated evolution in both human and chimpanzee lineages. Of special significance, despite the overrepresentation of these gene categories in both human and chimpanzee terminal lineages, these studies have found little overlap among the specific genes underlying these shared enriched annotations.…”
Section: Insights From Genesmentioning
confidence: 99%
“…Finally, recent genome-wide surveys indicate that non-coding cis -regulatory sequences in close proximity to genes involved in neuronal cell adhesion (Prabhakar et al 2006) and neurogenesis (Haygood et al 2007) have undergone accelerated evolution in both human and chimpanzee lineages. Of special significance, despite the overrepresentation of these gene categories in both human and chimpanzee terminal lineages, these studies have found little overlap among the specific genes underlying these shared enriched annotations.…”
Section: Insights From Genesmentioning
confidence: 99%
“…The role of natural selection in the evolution of gene regulation is hotly debated. Many researchers favor the idea that the evolution of gene expression is primarily driven by selection (Nuzhdin et al 2004;Gilad et al 2006a,b;Haygood et al 2007;Mustonen and Lassig 2007;Hutter et al 2008), with some studies advocating stabilizing selection or directional selection as more "important." However, a significant minority urge that the role of neutral evolution must not be neglected (Lynch 2007;Fay and Wittkopp 2008).…”
Section: The Evolution Of Gene Expressionmentioning
confidence: 99%
“…For this reason, new analytical techniques are being developed that are applicable to detecting adaptation in noncoding regions. [33][34][35][36]…”
Section: Integrated Functional Morphological Adaptations: Bipedalism mentioning
confidence: 99%